Traits of neighbouring plants and space limitation determine intraspecific trait variability in semi-arid shrublands - Luca Borger (Journal of Ecology, 2015)
Understanding how intraspecific trait variability (ITV) responds to both abiotic and biotic constraints is crucial to predict how individuals are assembled in plant communities, and how they will be impacted by ongoing global environmental change.Three key functional traits [plant height, leaf area (LA) and specific leaf area (SLA)] were assessed to quantify the range of ITV of four dominant plant species along a rainfall gradient in semi-arid Mediterranean shrublands. Variance partitioning and confirmatory multilevel path analyses were used to assess the direct and indirect effects of rainfall, space limitation (crowding) and neighbouring plant traits on ITV.The direct effect of the local neighbourhood on the trait values of subordinate individuals was as strong as the effect of rainfall. The indirect effect of rainfall, however, mediated by the effect of the local neighbourhood on the trait values of subordinate individuals, was weak. Rainfall decreased the height and SLA of subordinate individuals, but increased their LA. Neighbouring plant traits were just as strong predictors as crowding in explaining changes in ITV.Synthesis. Our study provides a framework to disentangle the direct effects of abiotic factors and their indirect effects on ITV mediated by the local neighbourhood. Our results highlight that abiotic and biotic constraints are both substantial sources of trait variations at the individual level, and can blur processes underlying changes in ITV. Considering and disentangling combined sources with an individual perspective would help to refine our predictions for community assembly and functional ecology.